2018
DOI: 10.1016/j.jid.2018.03.1517
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Atopic Dermatitis Colonized with Staphylococcus aureus Have a Distinct Phenotype and Endotype

Abstract: Patients with atopic dermatitis (AD) are commonly colonized with Staphylococcus aureus (AD S. aureus), but what differentiates this group from noncolonized AD patients (AD S. aureus) has not been well studied. To evaluate whether these two groups have unique phenotypic or endotypic features, we performed a multicenter, cross-sectional study enrolling AD S. aureus (n = 51) and AD S. aureus (n = 45) participants defined by the presence or absence of S. aureus by routine culture techniques and nonatopic, noncolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 62 publications
7
110
0
3
Order By: Relevance
“…Interestingly, a Cochrane review concluded that data was lacking for highly beneficial outcomes with exclusive use of antibiotics in the management of AD. This is consistent with studies dating back to the early 1970s by Leyden and Kligman that patients with AD primarily benefit from antibiotics when they are colonized with more than one million bacteria per cm of skin. Therefore, in the absence of an exudative or crusted skin lesion, the usefulness of antibiotics can be debated and their ability to completely eliminate S. aureus colonization is dubious.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, a Cochrane review concluded that data was lacking for highly beneficial outcomes with exclusive use of antibiotics in the management of AD. This is consistent with studies dating back to the early 1970s by Leyden and Kligman that patients with AD primarily benefit from antibiotics when they are colonized with more than one million bacteria per cm of skin. Therefore, in the absence of an exudative or crusted skin lesion, the usefulness of antibiotics can be debated and their ability to completely eliminate S. aureus colonization is dubious.…”
supporting
confidence: 89%
“…Atopic dermatitis (AD) is a pruritic chronic inflammatory skin disease associated with Staphylococcus aureus colonization . This is a clinically significant finding because S. aureus colonization is associated with increased AD severity, a more allergic diathesis and skin‐barrier dysfunction . This propensity toward S. aureus colonization is complex but begins with attachment of S. aureus to bacterial adhesion sites within the skin.…”
mentioning
confidence: 99%
“…The cutaneous microbiome, on the other hand, is clearly associated with AD, as a vast majority (>90%) of AD patients have their skin colonized with Staphylococcus aureus, compared to only 5% of healthy controls . In addition, S. aureus positive AD patients seem to have more severe disease, higher levels of Type 2 biomarkers (CCL17, POSTN), allergen sensitization (IgE), and barrier dysfunction (higher TEWL) than non‐colonized AD controls . Also, in a prospective study on children with AD, an increase in the proportion of S. aureus and a concomitant decrease in bacterial diversity preceded worsening (flare) of AD .…”
Section: From Disease Understanding To Biomarkers Endotypes and Tarmentioning
confidence: 98%
“…Compared to the noncolonized, S. aureus -colonized AD patients have more severe AD, higher blood eosinophil numbers, and higher total and allergen-specific IgE levels, as well as a greater barrier dysfunction as assessed by a transepidermal water loss and stratum corneum (SC) integrity that are not associated with filaggrin mutations [9]. …”
Section: Clinical Presentationmentioning
confidence: 99%